Jesus and the eyewitnesses : the Gospels as eyewitness testimony - Bauckham, Richard (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2017)
"This book argues that the four Gospels are closely based on the eyewitness testimony of those who personally knew Jesus. Noted New Testament scholar Richard Bauckham challenges the prevailing assumption that the accounts of Jesus circulated as "anonymous community traditions," asserting instead that they were transmitted in the names of the original eyewitnesses."--Jacket.
From the historical Jesus to the Jesus of testimony -- Papias on the eyewitnesses -- Names in the Gospel traditions -- Palestinian Jewish names -- The twelve -- Eyewitnesses "from the beginning" -- The Petrine perspective in Mark -- Anonymous persons in Mark's passion narrative -- Papias on Mark and Matthew -- Three models of oral tradition -- Transmitting the Jesus traditions -- Anonymous tradition or eyewitness testimony? -- Eyewitness memory -- The gospel of John as eyewitness testimony -- The witness of the beloved disciple -- Papias on John -- Polycrates and Irenaeus on John -- The Jesus of testimony -- Eyewitness in Mark (Revised) -- Who was the beloved disciple? (Continued) -- The end of form criticism (Confirmed)
Includes bibliographical references (pages 616-646) and indexes.
Keywords: Jesus Christ -- Historicity; Jesus Christ; Bible. -- Evidences, authority, etc; Bible; Authority -- Religious aspects; Historicity of Jesus Christ